FRASA NOMINA JAWA KUNA DALAM TEKS ADIPARWA - Apriani, Ni Ketut (Humanis, 2016)
Research " Clasic Javanese Noun Phrase In Text Adiparwa " aims to describe about understanding ,characteristics , structural and semantic relations of noun phrases in the text adiparwa Javanese . This study used structural linguistic theory put forward by Ferdinand de Saussure . The method in this study such as : include methods and techniques providing data , methods and data analysis techniques , methods and techniques of data presentation of results . The method of providing data using refer methods with library research methods . In analyzing the data using insert technique and substitution techniques while presentation  using informal and formal with inductive and deductive techniques . Noun phrase is an endocentric phrase that is main of nouns . Classification of noun phrases have seen from the syntactic structure intrafrasal , the noun phrase can differentce  into two noun phrases , the type of noun + noun and noun phrases , the type of non - noun + noun . Noun phrases clasic Javanese have a pattern N + N , N + Pron , Num + N , N + V, Pron + N, P + N. Noun semantic phrase relationif syntactic type noun + noun phrases compared to the type of noun phrase + non - nouns , then one thing that is very interesting is the relationship between the semantic are main noun and attributes noun with a noun in a noun + noun phrase type is flexible , compared to type phrases non - noun + noun .
Keywords: The phrase , structure , semantic , Hierarchy